EDUKASI PENGELOLAAN KEUANGAN DI ERA DIGITAL PADA MASYARAKAT DESA PANCURAN GADING KECAMATAN TAPUNG KABUPATEN KAMPAR - Primadayani, Syurti; Irawan, Dika; Azmi, Fauzan; Hidayat, Novit; Nurhayati, Nurhayati (Jurnal Pengabdian Kompetitif, 2025)
This service is based on the interest of the Service Team in financial management education and how to improve skills, knowledge, and in dealing with the economic community, because Management is a milestone in implementing an activity where the success of an activity depends on how the management or management of the activity is. In general, good Human Resources will greatly affect the social and economic aspects of a good society. The desired end result of this activity is how the Pancuran Gading Village Community, Tapung District, Kampar Regency in particular can understand and comprehend how to properly and correctly educate on Digital Era Financial Management and understand the impacts of not protecting the environment from an early age, and in the future it is hoped that there will be efforts made so that Digital Era Finance can be utilized by the community